Ammonia Emissions from Subalpine Forest and Mountain Grassland Soils in Rocky Mountain National Park. Issue 4 (1st July 2018) - Stratton, Joshua J.; Ham, Jay; Borch, Thomas
Abstract : Atmospheric deposition of NH3 and NH4 + contributes to eutrophication within sensitive subalpine ecosystems of Rocky Mountain National Park (RMNP) in the United States. However, little is known about the local contribution of NH3 from soils within the park. Thus, the goal of this study was to quantify and compare NH3 emissions from intact soil cores sampled from a subalpine grassland and forest within RMNP. Cores were collected at 2‐wk intervals from 20 June 2011 to 12 Sept. 2011 and transferred to a laboratory chamber system for NH3 flux measurements. Additionally, N wet deposition was monitored at the sampling location to investigate possible impacts on NH3 soil emissions. The average quantifiable NH3 emissions (with SDs) from intact soil cores analyzed in the laboratory (23°C) were 0.42 ± 0.30 mg NH3 –N m −2 d −1 for grassland soil and 0.21 ± 0.03 mg NH3 –N m −2 d −1 for forest soil ( p < 0.001). A mechanistic model was developed to estimate the impact of temperature on soil emissions using the chamber data and field‐site air temperatures. Average estimated NH3 emissions from the field site over the study period were 0.21 and 0.082 mg NH3 –N m −2 d −1 for grasslands and forests, respectively. Ammonium wet deposition was not correlated to short term reemission of NH3 based on N isotope analysis. This work provides new information on the magnitude of NH3 emissions from native subalpine soils, indicating that natural emissions are not likely major sources of NH3 in the RMNP airshed. Core Ideas: We assessed NH3 emissions from native subalpine soils in the RMNP. NH3 emissions from grassland and forest soils within RMNP were directly compared. NH3 emissions from forest soils were significantly lower than grassland soils. Natural NH3 emission from soils likely plays a minor role in NH4 + wet deposition in the RMNP.